Metabolic engineering of Saccharomyces cerevisiae by using the CRISPR-Cas9 system for enhanced fatty acid production. (October 2018) - Kim, Do Hyoung; Kim, In Jung; Yun, Eun Ju; Kwak, Suryang; Jin, Yong-Su; Kim, Kyoung Heon
Graphical abstract: Highlights: Saccharomyces cerevisiae were engineered to increase fatty acid production. Marker-free Cas9 was employed to increase the cytosolic acetyl-CoA pool. Total and unsaturated fatty acid levels increased as a result of the engineering. Cas9 was demonstrated an effective tool in generating fatty acid-producing yeast. Abstract: Fatty acids produced by the yeast, Saccharomyces cerevisiae, are not only industrially important products, but also highly affect fermentation efficiency. Despite that S. cerevisiae is the potent metabolic platform, traditional plasmid-based genetic manipulations still impose concerns about safety and environmental impact. In this study, using the Cas9 system, S. cerevisiae, was metabolically engineered for increased production of fatty acids by increasing cytosolic acetyl-CoA production via disrupting the isocitrate dehydrogenase gene of the TCA cycle and introducing the cytosolic ATP-citrate lyase gene from Yarrowia lipolytica . By expressing the ATP-citrate lyase gene from Y. lipolytica, total fatty acid production increased by 37.1% compared to that by the wild-type yeast. This total fatty acid production herein increased ∼2 times compared to that by an engineered S. cerevisiae in a previous report, and unsaturated fatty acid levels also increased. Our results suggest that the Cas9 system for S. cerevisiae could be applied to engineer the yeast for industrial production of bio-based products.